PENGARUH STRUKTUR MODAL, PERPUTARAN ASET TERHADAP KINERJA PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI: Bahasa Indonesia - Laurencia, Noviana; Indrati, Menik (Jurnal Riset Akuntansi Politala, 2024)
Company performance can be seen through financial reports. The uncertainty of NPM each year is a consideration to see the factors that have an influence. This research was conducted with the aim of exploring the impact of capital structure and asset turnover using company size as a moderating variable on company performance. There are 35 samples that meet the criteria from a total population of 57 companies with research objects as main board companies in the non-cyclical consumer sector for the period 2020 - 2022. This research uses the moderated regression analysis (MRA) method using the help of statistical analysis tools. The research results show that the variables capital structure, asset turnover, company size, company size which moderates capital structure, and company size which moderates asset turnover simultaneously influence company performance. The capital structure variable has a positive effect on company performance. The asset turnover variable has a negative effect on company performance. The company size variable is unable to moderate the influence of capital structure on company performance and the influence of asset turnover on company performance. This research can be a consideration for external parties to pay more attention to the size of the company's debt and see how effectively the company's assets can work, to maximize its performance. For companies to be able to make efforts to prevent increasing company risks and maximize resources to be able to utilize company assets optimally.